PENGARUH PENGAWASAN PREVENTIF, PENGAWASAN DETEKTIF DAN PENGANGGARAN BERBASIS KINERJA TERHADAP EFEKTIFITAS PENGENDALIAN ANGGARAN (STUDI EMPIRIS PADA SKPD KABUPATEN KUANTAN SINGINGI) - ', Azhari S '; ', Kamaliah; ', Jaka Hendrawan (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aims to look at the Effects of Preventive Monitoring, Surveillance Detective and Performance Based Budgeting Budgetary Control Effectiveness Against Empirical Study on Kuantan Singingi district offices. The population in this study are all within the district government offices Kuantan Singingi, Riau province, amounting to 29 offices. While the sample is employees who participate in the budgetary participation Kuantan Singingi District Government as a whole, amounting to 97 people. To test the hypothesis of the study used multiple regression analysis method with the help of SPSS software. The results show that preventive control does not significantly influence the effectiveness of budgetary control with a significance value of 0.124> 0.05. While the detective monitoring and performance-based budgeting significantly influence the effectiveness of budgetary control with empirical studies in the Kuantan Singingi district offices with significance 0.000 <0.05. Donations effect of preventive monitoring, supervision and performance-based budgeting detective on the effectiveness of budgetary control with empirical studies in the Kuantan Singingi district offices by 52.9%. Kata Kunci : Effect of Preventive Monitoring, Surveillance Detective, Performance Based Budgeting and Budgetary Control Effectiveness.